Analisis Bauran Pemasaran Terhadap Tingkat Penjualan Roti UD Nabila Bakery Di Desa Kalasey Kecamatan Mandolang - Saleh, Elvira R.; Rengkung, Leonardus Ricky; Rori, Yolanda Pinky Ivanna (AGRI-SOSIOEKONOMI, 2023)
This study aims to identify and analyze the application of the marketing mix in increasing sales at UD Nabila Bakery in Kalasey Village, Mandolang District. The method of data collection in this study uses primary data, where the primary data is obtained through interviews with 4(four) respondents which include product variations, price variations, sales condisitions and promotion. Meanwhile, secondary data was obtained through interviews with the owner of UD Nabila Bakery. The results of this study, it shows the application of the marketing mix in increasing sales volume at UD Nabila Bakery, namely in terms of products, the products produced are able to compete with competitors by always providing good quality both in terms of taste and texture of bread. In terms of price, UD Nabila Bakery sets a selling price that is relatively affordable considering its target market is from all walks of life. In terms of place/distribution channel, UD Nabila Bakery's bread has not been able to increase sales optimally due to competition for the same product, rising raw material prices and lack of expansion of the target market area, causing a decline in sales of the bread. And in terms of promotion, UD Nabila Bakery's bread still uses a simple promotion system, namely through word of mouth. So it has not been able to increase sales to the maximum. The increase in sales of UD Nabila Bakery's bread could occur because the product strategy and pricing strategy used were able to attract consumers to repurchase the products offered. With increasing consumer interest, there will be an increase in sales of UD Nabila Bakery's bread.